An automated rapid detection system using the quenching probe method for detecting interleukin 28B and inosine triphosphatase single nucleotide polymorphisms in chronic hepatitis C. Issue 4 (10th December 2012) - Takahashi, H.; Mizuta, T.; Oeda, S.; Isoda, H.; Nakashita, S.; Kawaguchi, Y.; Izumi, N.; Hirai, M.; Kurose, K.; Iwane, S.; Eguchi, Y.; Kimura, S.; et al.
Summary: Single nucleotide polymorphisms (SNPs) in the interleukin 28B gene ( IL28B ) are good pretreatment predictors of anti‐hepatitis C virus (HCV) therapy with interferon. SNPs of the inosine triphosphatase ( ITPA ) gene are associated with reduced haemoglobin levels during treatment with ribavirin. The i‐densy™ (Arkray, Inc.), which is based on the quenching probe (QP) method, automatically detects target genes in blood samples by fluorescence quenching within 100 min. Using a QP and primer set, a gene amplification response is generated that can quickly and easily detect a specific gene's arrangement by fluorometry. The present study was conducted to compare the utility of i‐densy (QP method) with that of conventional direct sequencing (DS) for detecting SNPs in the IL28B and ITPA genes in chronic hepatitis C patients. Between June 2011 and January 2012, 73 consecutive patients underwent genotyping of IL28B, and 54 patients underwent genotyping of ITPA. All of the patients were seropositive for HCV‐RNA. The IL28B and ITPA genotypes were tested for bi‐allelic polymorphisms in rs8099917 (T/T, T/G and G/G; minor allele, G) and rs1127354 (C/C, C/A and A/A; minor allele, A), respectively. The results obtained with the QP method were identical to those obtained with the conventional DS method. The frequency of the IL28B genotypes TT, GT and GG were 74%, 24.7% and 1.4%, respectively, and those of the ITPA genotypes CC, AC and AA were 68.5%, 29.6% and 1.9%, respectively. These results indicate that the i‐densy using the QP method can automatically, quickly and easily identify genotypes of IL28B and ITPA .